2012
DOI: 10.1111/j.1751-2980.2012.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal performance of simple noninvasive tests for advanced fibrosis in Chinese patients with nonalcoholic fatty liver disease

Abstract: Although slightly less accurate than liver biopsy, simple noninvasive tests can reliably exclude advanced fibrosis in Chinese NAFLD patients in our center. FIB-4 index performs better than the other tests under examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
2
30
1
1
Order By: Relevance
“…Nevertheless, fasting serum FFA constitute the majority of fatty acids delivered to the liver and contribute to liver fat metabolism and accumulation in NAFLD. Third, we used the FIB-4 index for evaluating advanced fibrosis of NAFLD according the studies of Xun YH et al56. FIB-4, a simple non-invasive index composed of readily available routine laboratory tests, can accurately predict advanced fibrosis and cirrhosis in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, fasting serum FFA constitute the majority of fatty acids delivered to the liver and contribute to liver fat metabolism and accumulation in NAFLD. Third, we used the FIB-4 index for evaluating advanced fibrosis of NAFLD according the studies of Xun YH et al56. FIB-4, a simple non-invasive index composed of readily available routine laboratory tests, can accurately predict advanced fibrosis and cirrhosis in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Although these tests are slightly less accurate than liver biopsy, these noninvasive tests can reliably exclude advanced fibrosis in a high proportion of NAFLD patients. The markers like NAFLD fibrosis score, FIB-4, and APRI scores can be used for the noninvasive diagnosis of fibrosis [36][37][38] . Some studies have shown that the diagnostic potential of circulating TIMP-1 is higher than that of serum ALT, AST or albumin values [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the FIB-4 score based on several laboratory tests can reliably predict advanced fibrosis and cirrhosis in NAFLD [48]. Recently, Xu et al [49] reported that a high FIB-4 score (≥1.100) is associated with an increased risk of prevalent CKD (eGFR <60 mL/min/1.73 m 2 ) and is an independent predictor of CKD in individuals with ultrasonography-diagnosed NAFLD [49].…”
Section: Discussionmentioning
confidence: 99%